2020
DOI: 10.2147/dddt.s243311
|View full text |Cite
|
Sign up to set email alerts
|

<p>Lentinan Inhibits AGE-Induced Inflammation and the Expression of Matrix-Degrading Enzymes in Human Chondrocytes</p>

Abstract: Background: Chondrocyte-mediated inflammation is an important pathological component of osteoarthritis (OA) development. There are currently no therapies that completely reverse the development of OA. Lentinan, a type of polysaccharide derived from Lentinus edodes, has been demonstrated to possess significant anti-viral, anti-cancer, and anti-inflammatory effects, and has been recently used in the treatment of several inflammatory diseases. However, little research has focused on the pharmacological effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Interestingly, the intervention with LNT showed an effective antagonism against arsenic-induced the elevations of IL-17A and inflammasomes NLRP3 in mice, indicating the downregulation in IL-17A secreted by Th17 cells, contributing to the amelioration of downstream NF-κB inflammatory signaling in hepatocytes and the attenuation of arsenic-induced hepatotoxicity in mice. Similarly, the previous studies showed that LNT reduces the activation of NF-κB and inhibits the production of pro-inflammatory cytokines IL-1β, TNF-α, IL-8 in chondrocytes [ 26 ], LNT intervention improves hepatic cell morphology by the decreased activity of NF-κB signal in rat’s liver with sepsis [ 27 ].…”
Section: Discussionmentioning
confidence: 72%
“…Interestingly, the intervention with LNT showed an effective antagonism against arsenic-induced the elevations of IL-17A and inflammasomes NLRP3 in mice, indicating the downregulation in IL-17A secreted by Th17 cells, contributing to the amelioration of downstream NF-κB inflammatory signaling in hepatocytes and the attenuation of arsenic-induced hepatotoxicity in mice. Similarly, the previous studies showed that LNT reduces the activation of NF-κB and inhibits the production of pro-inflammatory cytokines IL-1β, TNF-α, IL-8 in chondrocytes [ 26 ], LNT intervention improves hepatic cell morphology by the decreased activity of NF-κB signal in rat’s liver with sepsis [ 27 ].…”
Section: Discussionmentioning
confidence: 72%
“…It is reported that 24 or 48 h of 100 µg/mL AGE3 stimulation increases the expression levels of MMP1, MMP3, MMP13, ADAMTS4, and ADAMTS5 up to four-fold(Gao and Zhang 2019; Zhang et al 2020). In our experimental setup, 10 µg/mL AGE3 did not alter protease expression for 1-24 h or for one to eight weeks (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Lentinan (Figure 11), extracted from its fruiting body, has clinically significant anticancer, antibacterial, antiviral, and anticoagulant effects. There is a report on its preventive effects on skin oxidative damage by H 2 O 2 , reduction MDA formation, and increased SOD activity in HaCat cells [115] as well as on the inhibition of the production of proinflammatory cytokines, including IL-1β, TNF-α, IL-8 and the secretion of PGE 2 and NO, by reducing the expression of COX-2 and iNOS in AGE-challenged chondrocytes [116].…”
Section: Lentinus Edodesmentioning
confidence: 99%